Advanced Tribology Proceedings of CIST2008 & ITS-IFToMM2008 - Luo, Jianbin; Meng, Yonggang; Shao, Tianmin; Zhao, Qian.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Advanced Tribology" is the proceedings of the 5th China International Symposium on Tribology (held every four years) and the 1st International Tribology Symposium of IFToMM, held in Beijing 24th-27th September 2008. It contains seven parts: lubrication; friction and wear; micro/nano-tribology; tribology of coatings, surface and interface; biotribology; tribo-chemistry; industry tribology. The book reflects the recent progress in the fields such as lubrication, friction and wear, coatings, and precision manufacture etc. in the world. The book is intended for researchers, engineers and graduate students in the field of tribology, lubrication, mechanical production and industrial design. The editors Jianbin Luo, Yonggang Meng, Tianmin Shao and Qian Zhao are all the professors at the State Key Lab of Tribology, Tsinghua University, Beijing.
1. Lubrication -- 2. Friction and wear -- 3. Micro/Nano-tribology -- 4. Tribology of coatings, surface and interface -- 5. Biotribology -- 6. Tribo-chemistry -- 7. Industry tribology.
Keywords: Engineering; Chemistry, Physical organic; Mechanics; Mechanics, applied; Chemistry, inorganic; Engineering; Theoretical and Applied Mechanics; Mechanics; Tribology, Corrosion and Coatings; Physical Chemistry